2017
DOI: 10.18632/oncotarget.16462
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOTAIR acts as competing endogenous RNA to control the expression of Notch3 via sponging miR-613 in pancreatic cancer

Abstract: Pancreatic cancer is one of the most deadly cancers with a poor prognosis. Though studies have implicated the roles of microRNAs in pancreatic cancer progression, little is known about the role of miR-613 in pancreatic cancer. In the present study, the expression of miR-613 was down-regulated in pancreatic cancer tissues and cancer cell lines. Down-regulation of miR-613 was positively correlated with tumor differentiation, advanced TNM stage, nodal metastasis and shorter overall survival in patients with pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 36 publications
(43 reference statements)
3
63
0
Order By: Relevance
“…An increasing literature has evidenced that lncRNA can act as a ceRNA via sponging miRNA [13, 14]. Herein, we detected the cross-regulation between MEG3 and miR-183, since in a recent review, miR-183 has been reported as a pivotal miRNA in endocrine cancer metastasis [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing literature has evidenced that lncRNA can act as a ceRNA via sponging miRNA [13, 14]. Herein, we detected the cross-regulation between MEG3 and miR-183, since in a recent review, miR-183 has been reported as a pivotal miRNA in endocrine cancer metastasis [21].…”
Section: Resultsmentioning
confidence: 99%
“…In the cancer studies, miRNAs can function to be oncogenic or tumor-suppressive [13]. Besides, an increasing study have evidenced that lncRNAs can act as a competing endogenous RNA (ceRNA) via sponging miRNAs [13, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HOTAIR could bind to inter‐cellular miR‐331‐3p and miR‐124 based on its characteristic RNA sponging, thereby up‐regulating cancer cells’ capacity to reproduce 26. The sponging relationship between HOTAIR and miR‐613 was also manifested within carcinomas, such as non‐small cell lung cancer and pancreatic cancer 27, 28. The miR‐613 herein was suggested as a suppressor for retinoblastoma formation by targeting E2F5 29.…”
Section: Introductionmentioning
confidence: 99%
“…The aberrantly expressed lncRNAs have been found to be implicated in tumorigenesis and development of various cancers, including breast cancer [5]. Some wellstudied lncRNAs, such as H19, MALAT1 and HOTAIR have been reported to play oncogenic roles in the pathogenesis of tumors [6][7][8], whereas MEG3, GAS5 and BANCR could function as tumor suppressors [9][10][11]. However, the molecular mechanisms of lncRNAs underlying carcinogenesis and progression of triple-negative breast cancer remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%